ANALISIS KESALAHAN SISWA KELAS IX DALAM MENYELESAIKAN SOAL MATERI TEOREMA PYTHAGORAS - Idzni Nur Hafizah; Chandra Novtiar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Article is one of the research results written to analyzeor assess an activity that has a problem. This research is closely related to a problem that occurs in schools with certain materials.  The purpose of this study was to analyze the results of the students' mathematical understandingof pythagoras theorem material. Pythagoras material is a subject matter that must be mastered or understood by students with the purpose to add student insightinto the next material.   Therefore,  this research is very useful in assessing and knowing the extent to which students understand the material. This research was conducted to grade IX students of SMPN 2 Cibeber, the total number of students is  19 people consisting of 8 male students, and 11 female students. The research provided  results, that the ability of students are low in terms of understanding the problems given.